The value of conservative management in pediatric deep neck space infections - Joana Silva; José Penêda; Joana Ferreira; Sandra Gerós; Sandra Alves; Artur Condé (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Objective: To evaluate the role of medical treatment in pediatric deep neck space infection management.